2022
DOI: 10.1002/hep.32419
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐driven immunosuppression by Treg and type‐2 conventional dendritic cells in HCC

Abstract: Background and Aims Hypoxia is one of the central players in shaping the immune context of the tumor microenvironment (TME). However, the complex interplay between immune cell infiltrates within the hypoxic TME of HCC remains to be elucidated. Approach and Results We analyzed the immune landscapes of hypoxia‐low and hypoxia‐high tumor regions using cytometry by time of light, immunohistochemistry, and transcriptomic analyses. The mechanisms of immunosuppression in immune subsets of interest were further explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 42 publications
(80 reference statements)
1
51
0
Order By: Relevance
“…Disease Markers conventional dendritic cells in hepatocellular carcinoma [10]. These results indicated that hypoxia played important roles in the regulation of immune cells in cancers.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Disease Markers conventional dendritic cells in hepatocellular carcinoma [10]. These results indicated that hypoxia played important roles in the regulation of immune cells in cancers.…”
mentioning
confidence: 81%
“…For example, hypoxia was shown to be a dominant remodeler of the effector T cell surface proteome, relative to activation and regulatory T cell suppression [ 9 ]. Hypoxia was also found to drive immunosuppression by Treg and type-2 conventional dendritic cells in hepatocellular carcinoma [ 10 ]. These results indicated that hypoxia played important roles in the regulation of immune cells in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, hypoxic tumor regions are enriched in a variety of immunosuppressive cells that interfere with NK cell functions (see below), including (but not limited to): T REG cells [93][94][95], M2-like tumor-associated macrophages (TAMs) [96,97] and myeloid-derived suppressor cells (MDSCs) [98][99][100].…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…LncRNA CYB561D2 has been indicated to activate STAT3 and lead to the immunosuppression in brain tumor [29]. Meanwhile, hypoxia was a crucial factor driving immunosuppression in various tumors [30]. However, whether CYB561D2 and HK2 could exert similar roles under hypoxia in NEC should be further investigated.…”
Section: Discussionmentioning
confidence: 99%